Regulation of dynamic spatiotemporal inflammation by nanomaterials in spinal cord injury - Zeping Liu; Chunyu Xiang; Xu Zhao; Toshimi Aizawa; Renrui Niu; Jianhui Zhao; Fengshuo Guo; Yueying Li; Wenqi Luo; Wanguo Liu; Rui Gu (Journal of Nanobiotechnology, 2024)
Abstract Spinal cord injury (SCI) is a common clinical condition of the central nervous system that can lead to sensory and motor impairment below the injury level or permanent loss of function in severe cases. Dynamic spatiotemporal neuroinflammation is vital to neurological recovery, which is collectively constituted by the dynamic changes in a series of inflammatory cells, including microglia, neutrophils, and astrocytes, among others. Immunomodulatory nanomaterials can readily improve the therapeutic effects and simultaneously overcome various drawbacks associated with treatment, such as the off-target side effects and loss of bioactivity of immune agents during circulation. In this review, we discuss the role of dynamic spatiotemporal inflammation in secondary injuries after SCI, elaborate on the mechanism of action and effect of existing nanomaterials in treating SCI, and summarize the mechanism(s) whereby they regulate inflammation. Finally, the challenges and prospects associated with using nanotechnology to modulate immunotherapy are discussed to provide new insights for future treatment. Deciphering the intricate spatiotemporal mechanisms of neuroinflammation in SCI requires further in-depth studies. Therefore, SCI continues to represent a formidable challenge. Graphical abstract